Effects of agglomerate characteristics on their collision kernels in the free molecular regime. (January 2022) - Qian, Weijia; Kronenburg, Andreas; Hui, Xin; Lin, Yuzhen; Karsch, Maximilian
Abstract: Collision frequencies of fractal clusters need to be modelled to predict cluster growth due to agglomeration. Here, we utilize Langevin dynamics to accurately capture the movement and collision of fractal agglomerates with various morphologies that are characterized by their size, fractal dimension, lacunarity and shape anisotropy in the free molecular regime. The simulations include rotational and translational movement and potential interactions between the agglomerates. The agglomerates move subject to Brownian motion and the simulations are designed such that collision rates can be directly deduced. Results show that collision radii scale with gyration radius but are also dependent on all the other characteristics. The lacunarity increases the collision radii while shape anisotropy can decrease them. The fractal dimension can increase the collision radii and its effect is dominant. The increasing effect of van der Waals forces on the collision radii is also quantified and found to be independent of the size of the agglomerates. A new linear model is proposed to predict collision radii to within 2.5% accuracy. Highlights: Langevin dynamics for clusters of arbitrary morphology. Direct (model-free) computation of collision frequencies and collision radii. Functional dependencies of collision radii on agglomerate characteristics.